Development of Ethnoscience-Based Learning on Bugis Traditional Food in The 4th Grade IPAS Textbook in Elementary Schools - Adela, Dhea; Suprapmanto, Joko; Sehab, Nurhayati (Universitas Pendidikan Mandalika, 2025)
This research aims to develop a textbook based on local wisdom with an integration of ethnoscience learning about traditional Bugis food. This research used Research and Development with a 4D model which consists of four stages, namely define, design, develop and disseminate. The research subjects for the practicality test included 192 students of IV grade elementary school and 6 teachers from the school population in Pallangga District, Gowa Regency, South Sulawesi. The validity test of textbooks was judged by material experts, language experts and media experts. Based on the results of the analysis of the Gregory formula, it is stated that the validation coefficient for learning books by material experts, media experts and language experts was 1.00 with the content validity category being